Improving the Quality of Sardine Fish Oil by Degumming Using Sodium Cholride Solution - Dian Prima Christiani Hulu; Sugeng Heri Suseno; Uju Uju (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
The quality of fish oil is determined by some parameters such as primary and secondary grade oxidation, fatty acid profile and physical qualities which include viscosity, density, color and clarity. Sardine fish oil by-products of fish meal processing can be a source of polyunsaturated fatty acids (PUFAs), particularlyeicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Degumming is one of steps that can be carried out to improve the quality of sardine fish oil. The processing will help to reduce oxidation and eliminate the impurity of the oil that influence the quality of fish oil. The purpose of this study was to determine the effect of sodium chloride solution degumming on the quality of sardine fish oil to fulfill International Fish Oil Standard (IFOS). Fish oil purification was done by degumming of 5% H2O,  followedby sodium chloride solution with ratio of fish oil and sodium chloride solution were 1:1; 1:3, and 1:5. The sodium chloride solution concentrations of 5% and 8% for 20, 30 and 40 minutes. The next steps after degumming process were followed by alkali neutralization and bleached by absorbent. The best treatmentwas at  concentration of 5%  sodium chloride solution, ratio fish oil with sodium chloride solution 1:1 on a long time degumming processed 20 minutes. The best quality of fish oil, according to IFOS, was resulted from the treatments combination of free fatty acid 0.21±0.00%, peroxide value 0.43±0.06 mEq/kg, anisidin value 2.22±0.04 mEq/kg and total oxidation 3.11±0.14  mEq/kg.